EPIDERMAL CHARACTERS OF BACCHARIS (ASTERACEAE) SPECIES USED IN TRADITIONAL MEDICINE - FREIRE SUSANA E.; URTUBEY ESTRELLA; GIULIANO DANIEL A. (Caldasia)
A morphological study of 38 species of Baccharis used in traditional medicine was carried out to provide some epidermal characters that will contribute to the knowledge of the genus. The present study revealed: 1) seven different types of trichomes: conical, aseptate fl agellate, fi liform fl agellate, 1-armed, 2-4-armed, bulbiferous fl agellate, and glandular biseriate; 2) that 28 of the total of 38 species have trichomes in tufts; 3) six different types of stomata: anomocytic, anisocytic, cyclocytic, actinocytic, tetracytic, and staurocytic; 4) that some trichome types, such as 2-4-armed (B. dracunculifolia) and aseptate fl agellate branched (B. trinervis), show a high diagnostic value; 5) that the stomata types can be used to differentiate species with similar trichomes type (e.g. B. trimera and B. articulata). Illustrations of the studied characters are provided.